MAFIA AKAD DALAM PERBANKAN SYARIAH - Fathul Amin Aziz (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2017)
The concept of Islamic banking is good enough, but the findings are substantial deviations in sharia banking practices in the field, among which are related to the contract which is the business core of the sharia bank itself. This condition should not be allowed to be dragged down, because the practice of deviation done by some sharia banks in this case is similar to the engineering of the sharia contract namely the conjunction of the product with the packaging of sharia services. Understanding the agreement will be important morning sharia banking practitioners as well as transparency on Sharia banks in order to prevent potential